BENTUK-BENTUK LAYANAN BIMBINGAN DI SEKOLAH DASAR GMIT 05 ADANG - Dian Regina Tamara Plaimo; Dewi S. Maleikari, Yessy Mata, Fredrik Maata, Petrus Mau Tellu Dony, Jon Abraham Lalang Yame, Imanue (JIP: Jurnal Ilmu Pendidikan, 2025)
The purpose of this study was to examine the forms of guidance services at GMIT 05 Adang Elementary School, Adang Buom Village, Teluk Mutiara District, Alor Regency. The research technique used in this study was descriptive qualitative, with interviews with the fifth-grade homeroom teacher, Ms. Maria T. G. Herin S. Mat, and fifth-grade students at GMIT 05 Adang Elementary School, Adang Buom Village, Teluk Mutiara District, Alor Regency. The results of this study indicate that the homeroom teacher has provided guidance services in the classroom, and students have also received guidance services at GMIT 05 Adang Elementary School, grade five.